Designing interorganizational information systems for supply chain integration: a framework. Issue 1 (9th May 2016) - Kauremaa, Jouni; Tanskanen, Kari
Abstract : Purpose: – The purpose of this paper is to increase understanding on the essential managerial and technical decisions in the design of IOIS for supply chain integration (SCI). Toward this end, the authors elaborate on IOIS constructs in the SCI context, and propose a framework on the design of IOIS for SCI based on the current literature. Design/methodology/approach: – The paper draws from prior literature on interorganizational information systems (IOISs) and supply chain management (SCM), and builds a conceptual framework that is illustrated by empirical examples from three case studies of a ten-year research program that focussed on e-business in SCM. Findings: – Based on prior literature from several domains, the authors propose a framework, which combines the managerial viewpoints and the technical viewpoints for designing IOIS for SCI. The authors argue that these decisions form the basis for constructing three main elements of the IOIS for SCI design theory, namely, purpose and scope, design principles, and technical framework. Furthermore, the authors suggest that the real thread binding the decisions on all levels – purpose and scope; design principles; technical framework – is the flexible differentiation over use contexts, primarily over partners and focal interorganizational processes. Research limitations/implications: – The key limitation of this work is the propositional nature of the advanced framework. However, the framework is strongly grounded in prior literature and is illustrated by examples from three empirical studies. Practical implications: – The proposed framework provides a systematic tool for both the design and evaluation of the practical implementation of IOISs in SCI context. Furthermore, the results point explicitly to the implications of the benefits received from unilateral and bilateral modes of IOIS design. Originality/value: – The synthesized framework and the observation of the requisite differentiation over use context complement prior work from multiple domains by discussing both managerial and technical questions of IOIS deployment within a single conceptualization.